Increasing the Utilization of Health Facilities through Education: Case Study in Gentungang Village, West Bajeng District, Gowa Regency - Nur Muallima; Dara Ugi Aras; Juliani Ibrahim (I-Com: Indonesian Community Journal, 2024)
A vital component that supports human life's well-being is health. World Health Organization (WHO) and Indonesia's Law No. 36 of 2009 both define health as the state of being physically, mentally, spiritually, and socially. Another acknowledged basic human right is health. This study emphasizes the value of public health programs that target the general public and work to prevent and improve health. Nonetheless, the community has not made the best use of the healthcare facilities that are available. The purpose of this study is to raise public awareness of health care facilities and encourage greater usage of them. The approach is outreach through talks, panel discussions, and Q&A sessions. The results show that public awareness of health facilities is quite high, yet incomplete information leads to difficulties in using available facilities. In order to increase public awareness and trust in government health services, comprehensive education and clear information are essential.